FEATURES OF THE PROGRAM FOR PROMOTING THE IMAGE OF THE FOOTBALL CLUB «VOLYN» (Physical Culture and Sport: Scientific Perspective, 2025)
Image in sports in general and in football in particular is an ambiguous concept. On the one hand, the reputation of a professional football club is the same reputation of a company that works in the sports industry and offers consumers its product - a football spectacle. On the other hand, the image in the sports (football) industry has its own specifics, significantly different from other industries. But, as in any other industry, club successes and sports achievements are inextricably linked with corporate reputation and, in fact, are impossible without it. The formulation of the objectives of the article is to determine the features of the image promotion program of the football club "Volyn". Each stage includes a number of activities united by one idea, creating a clearly developed system in which the main goal of the image promotion program of the football club "Volyn" is implemented step by step. The first two stages imply the “movement” of target groups in search of what will be of greater interest to them: participation in sports tournaments or creative events. These stages are also a “lever” that will ultimately lead the target audience to the final third stage.The first stage includes holding sports (football) tournaments. This stage has a social focus, which consists in popularizing a healthy lifestyle among young people. The task at this stage is: to organize tournaments between educational institutions of the city of Lutsk and attract public attention. The second stage of the promotion program includes the launch of creative competitions and educational events. This stage involves several approaches: creative, entertaining, educational, informational. The third stage includes a set of events that are part of an interactive platform aimed at reaching not only target groups, but also all fans in general.Thus, the measures that make up the promotion program are aimed at improving the image of the organization in the eyes of the general public and increasing loyalty among target groups. All measures are logically justified and simple to implement. The proposed measures are most likely to have a positive impact on the perception of the activities of the Volyn football club by consumers. Carrying out these measures will allow attracting new target groups as consumers of a "specific product", which will also have a positive impact on the economic component of the organization.
Keywords: image; football; stage; program; measures